Question
upstudy study bank question image url

1. \( \frac{3 x}{2}-\frac{x}{4}=1 \frac{1}{4} \) 3. \( \frac{3}{5}-\frac{7}{x}=\frac{7}{4}-\frac{5}{4 x} \) 5. \( \frac{1-x}{2}+\frac{2-x}{3}+1 \frac{1}{3}=0 \) 7. \( \frac{x-1}{2}-\frac{1}{2}=\frac{2 x-5}{2} \)

Ask by Mitchell Parsons. in South Africa
Feb 18,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions to the equations are: 1. \( x = 1 \) 2. \( x = -5 \) 3. \( x = 3 \) 4. \( x = 3 \)

Solution

Solve the equation \( \frac{3x}{2}-\frac{x}{4}=1\frac{1}{4} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{3x}{2}-\frac{x}{4}=1\frac{1}{4}\) - step1: Convert the expressions: \(\frac{3x}{2}-\frac{x}{4}=\frac{5}{4}\) - step2: Multiply both sides of the equation by LCD: \(\left(\frac{3x}{2}-\frac{x}{4}\right)\times 4=\frac{5}{4}\times 4\) - step3: Simplify the equation: \(5x=5\) - step4: Divide both sides: \(\frac{5x}{5}=\frac{5}{5}\) - step5: Divide the numbers: \(x=1\) Solve the equation \( \frac{3}{5}-\frac{7}{x}=\frac{7}{4}-\frac{5}{4x} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{3}{5}-\frac{7}{x}=\frac{7}{4}-\frac{5}{4x}\) - step1: Find the domain: \(\frac{3}{5}-\frac{7}{x}=\frac{7}{4}-\frac{5}{4x},x\neq 0\) - step2: Multiply both sides of the equation by LCD: \(\left(\frac{3}{5}-\frac{7}{x}\right)\times 20x=\left(\frac{7}{4}-\frac{5}{4x}\right)\times 20x\) - step3: Simplify the equation: \(12x-140=35x-25\) - step4: Move the expression to the left side: \(12x-35x=-25+140\) - step5: Add and subtract: \(-23x=-25+140\) - step6: Add and subtract: \(-23x=115\) - step7: Change the signs: \(23x=-115\) - step8: Divide both sides: \(\frac{23x}{23}=\frac{-115}{23}\) - step9: Divide the numbers: \(x=-5\) - step10: Check if the solution is in the defined range: \(x=-5,x\neq 0\) - step11: Find the intersection: \(x=-5\) Solve the equation \( \frac{1-x}{2}+\frac{2-x}{3}+1\frac{1}{3}=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{1-x}{2}+\frac{2-x}{3}+1\frac{1}{3}=0\) - step1: Convert the expressions: \(\frac{1-x}{2}+\frac{2-x}{3}+\frac{4}{3}=0\) - step2: Multiply both sides of the equation by LCD: \(\left(\frac{1-x}{2}+\frac{2-x}{3}+\frac{4}{3}\right)\times 6=0\times 6\) - step3: Simplify the equation: \(15-5x=0\) - step4: Move the constant to the right side: \(-5x=0-15\) - step5: Remove 0: \(-5x=-15\) - step6: Change the signs: \(5x=15\) - step7: Divide both sides: \(\frac{5x}{5}=\frac{15}{5}\) - step8: Divide the numbers: \(x=3\) Solve the equation \( \frac{x-1}{2}-\frac{1}{2}=\frac{2x-5}{2} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{x-1}{2}-\frac{1}{2}=\frac{2x-5}{2}\) - step1: Multiply both sides of the equation by LCD: \(\left(\frac{x-1}{2}-\frac{1}{2}\right)\times 2=\frac{2x-5}{2}\times 2\) - step2: Simplify the equation: \(x-2=2x-5\) - step3: Move the expression to the left side: \(x-2x=-5+2\) - step4: Add and subtract: \(-x=-5+2\) - step5: Add and subtract: \(-x=-3\) - step6: Change the signs: \(x=3\) The solutions to the given equations are: 1. \( x = 1 \) 2. \( x = -5 \) 3. \( x = 3 \) 4. \( x = 3 \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve the first equation, \( \frac{3x}{2} - \frac{x}{4} = 1 \frac{1}{4} \), let's convert the mixed number into an improper fraction: \( 1 \frac{1}{4} = \frac{5}{4} \). Now, multiply every term by 4 to eliminate the fractions: \[ 4 \left( \frac{3x}{2} \right) - 4 \left( \frac{x}{4} \right) = 4 \cdot \frac{5}{4} \] This simplifies to: \[ 6x - x = 5 \] So, \( 5x = 5 \) or \( x = 1 \). For the third equation, \( \frac{3}{5} - \frac{7}{x} = \frac{7}{4} - \frac{5}{4x} \), we first find a common denominator for the fractions. Multiplying through by \( 20x \) (the least common multiple of the denominators) will do the trick. This yields: \[ 12x - 140 = 35x - 25 \] Rearranging gives \( 25 = 23x \), or \( x = \frac{25}{23} \). For the fifth equation, we need to deal with \( \frac{1 - x}{2} + \frac{2 - x}{3} + 1 \frac{1}{3} = 0 \). Transform \( 1 \frac{1}{3} \) into an improper fraction: \( \frac{4}{3} \). We clear the fractions by multiplying by 6 (LCM of 2 and 3): \[ 3(1 - x) + 2(2 - x) + 8 = 0 \] This simplifies to \( 3 - 3x + 4 - 2x + 8 = 0 \), resulting in \( 15 - 5x = 0 \), or \( x = 3 \). For the seventh equation, \( \frac{x - 1}{2} - \frac{1}{2} = \frac{2x - 5}{2} \), we can multiply through by 2 to eliminate the fractions: \[ x - 1 - 1 = 2x - 5 \] This simplifies to \( x - 2 = 2x - 5 \). Rearranging gives \( x = 3 \). To sum it up, \( x \) values are: 1: \( x = 1 \) 3: \( x = \frac{25}{23} \) 5: \( x = 3 \) 7: \( x = 3 \)

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy